The level of mastery of the tenth grade students in the Sultanate of Oman of critical listening skills - Haron, Sueraya Che; Alkalbani, Khalid Rashid Ali (Journal of Curriculum and Teaching Methodology, 2022)
The study aimed to measure the level of mastery of the tenth grade students in the critical listening skills assigned to them, and to know the relationship between their level in it with the variable (sex). The study sample consisted of (447) male and female students. To achieve the objectives of the study, the researchers prepared a test to measure critical listening skills based on the critical listening skills prescribed for tenth grade students and approved in the Arabic Language Standards Document and related to the objectives and content of My Beautiful Language. To obtain the results, percentages, arithmetic averages, and t-test were used as appropriate statistical treatments. The results of the study showed that there is a weakness in the level of mastery of the tenth grade students in critical listening skills. Where (71%) of the study sample students were unable to master critical listening skills. The results also showed a low level of students’ mastery of critical listening skills in each skill separately. In addition, the results showed that there were statistically significant differences between the mean scores of students in the critical listening skills test according to the gender variable, in favor of females. The study recommended the need to develop the listening curriculum by focusing on developing critical listening skills for tenth grade students at the conclusion of basic education. The study also included a number of recommendations and suggestions for developing the teaching of critical listening skill in the light of its findings.